PERSEKUTUAN DEWASA MUDA KONTEKSTUAL YANG PEDULI ISU KESEHATAN MENTAL DI GEREJA KRISTEN INDONESIA (GKI) BROMO - Vania Sharleen Setyono; Jeanette Josephine Mintardjo; Christiani Pratika Pingkan (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2023)
Koinonia is one of the vocations of the church. As a good fellowship of believers, each individual in the congregation should be seen as a holistic human with four main aspects: physical, mental, social, and spiritual. This research examines mental health issues, specifically the Quarter Life Crisis experienced by the young adult congregation of GKI Bromo. By conducting field research using community-based action research (CBAR), the method found that the young adults of GKI Bromo were struggling with mental health issues in the context of building the congregation. It was necessary to design a fellowship involving the human mental aspect. The fellowship needs to concern and accommodate young adults to share their real experiences and give them space to do individual reflection. The follow-up action needed to be based on the findings of this research is that GKI Bromo needs to create a forum that facilitates contextualized peer support groups of young adults.